Choosing wisely in adult hospital medicine: Five opportunities for improved healthcare value. Issue 9 (19th August 2013) - Bulger, John; Nickel, Wendy; Messler, Jordan; Goldstein, Jenna; O'Callaghan, James; Auron, Moises; Gulati, Mangla
Abstract : BACKGROUND: In an effort to lead physicians in addressing the problem of overuse of medical tests and treatments, the American Board of Internal Medicine Foundation developed the Choosing Wisely campaign. The Society of Hospital Medicine (SHM) joined the initiative to highlight the need to critically appraise resource utilization in hospitals. METHODS: The SHM employed a staged methodology to develop the adult Choosing Wisely list. This included surveys of the organization's leaders and general membership, a review of the literature, and Delphi panel voting. RESULTS: The 5 recommendations that were subsequently approved by the SHM Board are: (1) Do not place, or leave in place, urinary catheters for incontinence or convenience or monitoring of output for non–critically ill patients (acceptable indications: critical illness, obstruction, hospice, perioperatively for <2 days for urologic procedures; use weights instead to monitor diuresis). (2) Do not prescribe medications for stress ulcer prophylaxis to medical inpatients unless at high risk for gastrointestinal complications. (3) Avoid transfusions of red blood cells for arbitrary hemoglobin or hematocrit thresholds and in the absence of symptoms or active coronary disease, heart failure, or stroke. (4) Do not order continuous telemetry monitoring outside of the intensive care unit without using a protocol that governs continuation. (5) Do not perform repetitive complete blood count and chemistry testing in the face of clinical and lab stability. CONCLUSIONS: Hospitalists have many opportunities to impact overutilization of care. The adult hospital medicine Choosing Wisely recommendations offer an explicit starting point for eliminating waste in the hospital. Journal of Hospital Medicine 2013;8:486–492. © 2013 Society of Hospital Medicine